2018
DOI: 10.1111/nyas.13549
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in the regulation of yeast life span

Abstract: The goal of the aging field is to develop novel therapeutic interventions that extend human health span and reduce the burden of age-related disease. While organismal aging is a complex, multifactorial process, a popular theory is that cellular aging is a significant contributor to the progressive decline inherent to all multicellular organisms. To explore the molecular determinants that drive cellular aging, as well as how to retard them, researchers have utilized the highly genetically tractable budding yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 105 publications
(165 reference statements)
1
46
0
Order By: Relevance
“…Furthermore, three genes related to amino acids synthesis (APE4, ARO1 and ARO7) and four genes involved in lipid homeostasis (ARV1, SRF1, NEM1 and LEM3), were all required for zinc tolerance. The SNARE (soluble N-ethylmaleimide-sensitive factor attached protein receptor) complex, a protein complex involved in membrane fusion, is also required for autophagy (Tyler and Johnson 2018). In this study, six genes (VAM7, VPS33, VPS51, SEC22, GOS1 and VPS45) encoding proteins belong to the SNARE complex were identified sensitive to zinc stress, indicating their crucial role in the process of autophagy under excess zinc conditions.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, three genes related to amino acids synthesis (APE4, ARO1 and ARO7) and four genes involved in lipid homeostasis (ARV1, SRF1, NEM1 and LEM3), were all required for zinc tolerance. The SNARE (soluble N-ethylmaleimide-sensitive factor attached protein receptor) complex, a protein complex involved in membrane fusion, is also required for autophagy (Tyler and Johnson 2018). In this study, six genes (VAM7, VPS33, VPS51, SEC22, GOS1 and VPS45) encoding proteins belong to the SNARE complex were identified sensitive to zinc stress, indicating their crucial role in the process of autophagy under excess zinc conditions.…”
Section: Discussionmentioning
confidence: 61%
“…Of these genes, mutants for 8 genes (PTC6, VTC2, GCN2, CCZ1, GCN1, VTC4, PHO85 and VPS45) accumulated higher intracellular zinc than wide-type cells, indicating their important roles in maintaining the intracellular zinc homeostasis. The only identified gene ATG gene in this study, ATG22, encodes a protein involved in transporting small molecules such as amino acids back to the cytosol for protein synthesis and other cellular functions (Tyler and Johnson 2018). Three genes of CCZ1, MON1 and YPT6 were required for the CVT pathway and the autophagy (Cabrera et al 2014;Suda et al 2013).…”
Section: Elevated Intracellular Zinc Levels Evoked By Excess Zincmentioning
confidence: 85%
See 1 more Smart Citation
“…Many of the genes and mechanisms are highly conserved in metazoans, including humans, with abnormalities in higher eukaryote autophagy resulting in the development of aging and age-related diseases, as previously reviewed 29 33 . Elsewhere, we have recently reviewed the contributions of autophagy to yeast lifespan extension 34 . Here, we synthesize the recent studies that link the ISR to lifespan extension in yeast, to support our proposal that the mechanism whereby stress extends lifespan is via induction of the ISR and downstream stress response pathways, including autophagy.…”
Section: Introduction To the Yeast Integrated Stress Responsementioning
confidence: 99%
“…Nonetheless, it remains unresolved whether impaired proteolytic function in alkalizing vacuoles is a driving force in aging. Recent literature, however, links the integrative stress response in yeast with enhanced replicative lifespan and autophagy ( Postnikoff et al 2017 ; Tyler and Johnson 2018 ). To address the question of whether proteolytic dysfunction in old, alkalized vacuoles plays a role in aging, we monitored the proteolytic degradation of a human protein in aging yeast cells that forms inclusions in patients with a variety of neurodegenerative diseases (α-synuclein; Yang and Yu 2016 ) and observed that aggregates accumulated within vacuoles as cells age.…”
mentioning
confidence: 99%